2001
DOI: 10.1177/000992280104000403
|View full text |Cite
|
Sign up to set email alerts
|

Injury Reduction and Bounce Characteristics of Safety Baseballs and Acceptability by Youth Leagues

Abstract: The only reasonable way to reduce the potential for ball-related youth baseball injuries sustained by the defensive players (the majority of ball-related injuries) is to make the ball less injurious. The American Academy of Pediatrics' 1994 statement on youth baseball injuries in this regard reads, "Consideration should be given to utilizing low-impact NOCSAE-approved baseballs and softballs for children 5 to 14 years of age, if these balls demonstrate satisfactory playing characteristics and reduce injury ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Field players: Baseball hardness Both animal and clinical studies have High [12,42,[43][44][45] demonstrated that harder baseballs result in more injuries and a higher risk of commotio cordis. Fixed bases [46,47] Intervention trials have demonstrated High that fixed bases result in far more lower extremity injuries than breakaway bases.…”
Section: Extrinsic Risk Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Field players: Baseball hardness Both animal and clinical studies have High [12,42,[43][44][45] demonstrated that harder baseballs result in more injuries and a higher risk of commotio cordis. Fixed bases [46,47] Intervention trials have demonstrated High that fixed bases result in far more lower extremity injuries than breakaway bases.…”
Section: Extrinsic Risk Factorsmentioning
confidence: 99%
“…Impact trauma from the baseball or a baseball bat is a common cause of injury during competition. Efforts have been made to decrease the hardness of baseballs used among younger players in an effort to reduce the frequency of contusions, fractures, and most importantly, commotio cordis [12,44]. Despite the laboratory-based efficacy of these softer baseballs at reducing the likelihood of impact trauma, 2 cases of commotio cordis have been reported after chest wall contact with a reduced-impact baseball [43].…”
Section: Extrinsic Factorsmentioning
confidence: 99%
See 3 more Smart Citations